Determination of ovulation in women using saliva ferning test - Ersyari, Riska Mutia; Wihardja, Rosiliwati; Dardjan, Murnisari (Padjadjaran Journal of Dentistry, 2014)
Every human being experiences growth and development, starting from childhood to adulthood. Women who have entered puberty will experience monthly menstrual cycle. One phase of the menstrual cycle is ovulation or the fertile phase of a woman. The fertile period is the period in which there is an egg ready to be fertilized by sperm. At the time of fertility, there is an increase in the amount of estrogen and progesterone hormones. Increase in these hormones is also found in saliva. Saliva as a biological fluid in the body can be used as a diagnostic fluid. Woman’s fertile period can be assessed from the saliva. Saliva containing high estrogen hormones can form a ferning picture on saliva dried on object glass. The type of research is the study of literature. A literature study was conducted to discuss the determining of the fertile woman with saliva ferning test. The results of previous studies showed the existence of differences in saliva pictures at the time of the fertile period and the infertile period. Salivary ferning was very clearly seen in the woman’s fertile period.